Non-elite Women Candidate and Middle Pathway in Indonesia's 2024 Local Election - Harahap, Raegen; Anisyah, Siti; Sattar, Yasmin (Journal of Local Government Issues, 2025)
In Southeast Asia, women's political representation is often explained through dynastic ties or grassroots activism. This article examines non-elite women candidates in the 2024 Legislative Election in Ogan Ilir, Indonesia, using Choi's "middle pathway" framework. In contrast to the dynastic and grassroots paths, the middle path emphasizes the conversion of family reputation, business networks, and social capital into political legitimacy. With a qualitative case study approach, this study shows how non-elite women candidates mobilized their father's philanthropic reputation as a local entrepreneur, transformed a family multipurpose building into a community political center, and used digital strategies to gain the highest votes in their constituencies. These findings broaden the debate about the representation of non-elite women in Indonesia by asserting that electability does not only depend on political dynasties or short-term patronage, but can also be built through political entrepreneurship strategies based on family reputation, economic networks, and candidate tenacity. Thus, the middle path presents an alternative for non-elite women to negotiate political legitimacy in the context of a local democracy that is still patriarchal.